2002
DOI: 10.1007/s00203-002-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The operon of the putative lactobacillar oligopeptide transport system (Opp) from Lactobacillus delbrueckii subsp. bulgaricus B14 was cloned and characterized. The opp operon was found to consist of five genes, oppD, oppF, oppB, oppC and oppA (1). In addition, an oppA (1) homolog, oppA (2), was found downstream of the operon. Sequence comparisons of the L. delbrueckii subsp. bulgaricus Opp system with other bacterial transport systems revealed the highest similarity to the oligopeptide transport system of Lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…OppA is an externally exposed extracellular lipoprotein carrying a peptidase II signal for covalent anchoring to the membrane [12] to which diverse roles have been ascribed; it acts as the substrate-binding protein of the oligopeptide transport system in lactobacilli [60], but has also been implicated in cytoadhesion of Mycobacterium hominis and Treponema denticolaria to eukaryotic cells through interaction with plasminogen and fibronectin respectively [61-63]. Furthermore, it has been found to interact with fibronectin and collagen in Lactobacillus casei BL23 and other OppA orthologues from lactobacilli such as MapA from L. reuteri are able to interact with Caco-2 [12,64].…”
Section: Discussionmentioning
confidence: 99%
“…OppA is an externally exposed extracellular lipoprotein carrying a peptidase II signal for covalent anchoring to the membrane [12] to which diverse roles have been ascribed; it acts as the substrate-binding protein of the oligopeptide transport system in lactobacilli [60], but has also been implicated in cytoadhesion of Mycobacterium hominis and Treponema denticolaria to eukaryotic cells through interaction with plasminogen and fibronectin respectively [61-63]. Furthermore, it has been found to interact with fibronectin and collagen in Lactobacillus casei BL23 and other OppA orthologues from lactobacilli such as MapA from L. reuteri are able to interact with Caco-2 [12,64].…”
Section: Discussionmentioning
confidence: 99%
“…The system was also genetically characterized in L. delbrueckii subsp. bulgaricus, where an extra homolog gene oppA2 is present [241]. The Opp system of other LAB was not widely investigated, but Liu et al [231] found the genes for the Opp system in several strains of L. acidophilus, L. brevis, L. casei, L. rhamnosus, L. johnsonii, L. gasseri, and L. helveticus.…”
Section: Transport System and Peptidasesmentioning
confidence: 99%
“…Similar to the oligopeptide transporters found in other Gram-positive bacteria, both the app and opp regions encode an apparent extracellular substrate binding protein (appA and oppA), two apparent integral membrane permeases (appBC and oppBC), and two apparent cytoplasmic ATPbinding proteins (appDF and oppDF). Orthologs of the opp and app oligopeptide transporters are common to many bacterial species, and often, two or more analogous transport systems are encoded by the genomes of Gram-positive bacteria (17,(55)(56)(57)(58). In …”
Section: Identification Of Opp and App Transporters In C Difficilementioning
confidence: 99%